Effect of liming on basic exchangeable cations of soil - Kaila, Armi (Agricultural and Food Science, 1974)
The effect of liming on the basic exchangeable cations in a sand, a heavy clay and a muddy clay soil was studied with a 9 month’s incubation experiment under laboratory conditions. Besides, observations were made in connection with some other incubation and field experiments. It was found that application of CaCO3 in amounts which reduced the acidity to about pH 7. decreased the content of exchangeable Mg in all experiments, and even a lower application effectively prevented any net release of nonexchangeable Mg which occurred in the muddy clay samples incubated without lime. Some fixation of K was also usually detected, but liming increased the amount of exchangeable Na. Essential differences apparently exist between the mechanisms of the retention of Mg and K induced by liming: Significantly lower amounts of Mg was extracted by 0.5 HCI from the limed samples of the heavy clay and muddy clay soil than from the original ones, while the contrary was true with K. The mechanisms connected with the Mg fixation were discussed. Attention was paid to the possibility that the usually poor Mg supporting ability of Finnish muddy clay soils may be partly connected with the heavy liming necessary for the cultivation of these acid soils.